Non-expected-utility based risk attitudes of Singaporeans - Ker, Hui Nee. (2008)
The research encompasses the study of non expected risk attitudes of Singaporeans based on the various paradoxes and non expected utility based theories namely the Prospect Theory, framing effect, reflection effect, isolation effect etc.